Mr. Selfridge. [Season 1] [videorecording (DVD)] - Davies, Andrew, 1936-; Piven, Jeremy; Goodman-Hill, Tom; O'Connor, Frances, 1967-; Tapper, Zoë, 1981-; Woodhead, Lindy (PBS Distribution, 2013)
Emmy Award-winning actor Jeremy Piven stars as American entrepreneur and colorful retail magnate Harry Gordon Selfridge. Pioneering and reckless, with an almost manic energy, Harry Selfridge created a theater of retail for early 1900s Londoners where any topic or trend that was new, exciting, entertaining-or sometimes just eccentric-was showcased. Based on the book Shopping, Seduction and Mr. Selfridge by author Lindy Woodhead.